Idiopathic linear IgA bullous dermatosis: prognostic factors based on a case series of 72 adults. (15th May 2017) - Gottlieb, J.; Ingen‐Housz‐Oro, S.; Alexandre, M.; Grootenboer‐Mignot, S.; Aucouturier, F.; Sbidian, E.; Tancrede, E.; Schneider, P.; Regnier, E.; Picard‐Dahan, C.; Begon, E.; Pauwels, C.; et al.
Summary: Background: Linear IgA bullous dermatosis (LABD) is a clinically and immunologically heterogeneous, subepidermal, autoimmune bullous disease (AIBD), for which the long‐term evolution is poorly described. Objectives: To investigate the clinical and immunological characteristics, follow‐up and prognostic factors of adult idiopathic LABD. Methods: This retrospective study, conducted in our AIBD referral centre, included adults, diagnosed between 1995 and 2012, with idiopathic LABD, defined as pure or predominant IgA deposits by direct immunofluorescence. Clinical, histological and immunological findings were collected from charts. Standard histology was systematically reviewed, and indirect immunofluorescence (IIF) on salt‐split skin (SSS) and immunoblots (IBs) on amniotic membrane extracts using anti‐IgA secondary antibodies were performed, when biopsies and sera obtained at diagnosis were available. Prognostic factors for complete remission (CR) were identified using univariate and multivariate analyses. Results: Of the 72 patients included (median age 54 years), 60% had mucous membrane (MM) involvement. IgA IIF on SSS was positive for 21 of 35 patients tested; 15 had epidermal and dermal labellings. Immunoelectron microscopy performed on the biopsies of 31 patients labelled lamina lucida (LL) (26%), lamina densa (23%), anchoring‐fibril zone (AFz) (19%) and LL+AFz (23%). Of the 34 IgA IBs, 22 were positive, mostly for LAD‐1/LABD97 (44%) and full‐length BP180 (33%). The median follow‐up was 39 months. Overall, 24 patients (36%) achieved sustained CR, 19 (29%) relapsed and 35% had chronic disease. CR was significantly associated with age > 70 years or no MM involvement. No prognostic immunological factor was identified. Conclusions: Patients with LABD who are < 70 years old and have MM involvement are at risk for chronic evolution. Abstract : What's already known about this topic? Linear IgA bullous dermatosis (LABD) is characterized by pure or predominant IgA deposits at the dermoepidermal junction. In adults, the clinical presentation is heterogeneous and antigen targets vary widely. Although LABD has a reputation for being a benign disease, its long‐term evolution remains unknown, especially in adults. What does this study add? Based on one of the largest analysed series of adult patients with idiopathic LABD, immunoelectron microscopy and immunological findings confirmed the wide diversity of LABD, overlapping with IgA‐related bullous pemphigoid, cicatricial pemphigoid and epidermolysis bullosa acquisita. One‐third of the patients achieved sustained complete remissions and two‐thirds had chronic or relapsing disease. Age > 70 years and absence of mucous membrane involvement were significantly associated with complete remission. What are the clinical implications of the work? Autoimmune bullous disease in patients < 70 years old, with mucous membrane involvement and pure or predominant linear IgA deposits at the dermoepidermal or chorioepithelial junction, supporting a diagnosis of LABD, are significantly more likely to have a chronic evolution. Respond to this article Linked Comment: Ishii. Br J Dermatol 2017;177 :16–17